engaruh Pembelajaran Berbasis Literasi Digital Terhadap Motivasi Dan Hasil Belajar Kognitif di MTs N Mojosari dan MTs N Sooko Mojokerto - Sudar Kajin (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
Learning based on Digital Literacy is learning that applies functional skills to digital media so as to be able to find and select relevant information, evaluate critically, be creative, collaborate with others, communicate effectively, and pay attention to aspects of electronic security and socio-cultural contexts that are increasingly developing in the luast community. The objectives of this study were: 1) To find out the differences in learning motivation of MTs N Mojosari students and Sooko Mojokerto MTs N by using Digital Literacy-based learning. 2) To determine the differences in cognitive learning outcomes of MTs N Mojosari students and Sooko Mojokerto MTs N by using Digital Literacy-based learning. 3) To determine the interaction of learning using Digital Literacy based on motivation and cognitive learning outcomes in MTs N Mojosari and MTs N Sooko Mojokerto. The results of the analysis can be summarized as follows: 1) From the results of the analysis it is known that Digital Literacy-based learning influences motivation in MTs N Mojosari Mojokerto gets a Fcount of 616,286 (significance F = 0,000). And in Sooko MTs N Mojokerto got Fcount 655,544 (significance F = 0,000), then the Zero Hypothesis (H0) was rejected and the Working Hypothesis (H1) was accepted. 2) From the results of the analysis it is known that the vision of Digital Literacy-based learning has an effect on cognitive learning outcomes in MTs N Mojosari Mojokerto obtained Fcount 6.398 (significance F = 0.013). And in Sooko Mojokerto MTs N, the value of Fcount is 8.041 (significance F = 0.007), then the Zero Hypothesis (H0) is rejected and the Working Hypothesis (H1) is accepted, 3) There is an interaction of Digital Literacy based learning on motivation and cognitive learning outcomes in MTs N Mojosari and Sooko Mojokerto MTs N Digital Literacy-based learning interactions on motivation in MTs N Mojosari amounted to 0.593 (59.3%), Dlanggu Mojokerto 1 Junior High at 0.217 (21.7%). While the cognitive learning outcomes at MTs N Mojosari were 0.869 (86.9%), in MTs N Sooko Mojokerto was 0.334 (33.4%)